Effectiveness of digital health in improving pregnancy quality among preconception women: A systematic review - Nurleli, Nurleli; Hadju, Veni; Indriasari, Rahayu; Areni, Intan S.; Masni, Masni; Riskyani, Shanti (Narra Sains Indonesia, 2025)
Improving nutrition in women prior to conception represents an alternative approach to enhancing the quality of pregnancy. Increased knowledge and self-efficacy among preconception women positively impact changes in health behavior. The rapid development of technology provides an opportunity to implement innovative interventions, including digital health. The aim of this study was to systematically review the efficacy of digital health interventions in modifying the behavior of preconception women. The data were obtained by searching relevant articles published from 2015 to 2023 in electronic databases, including Google Scholar, Science Direct, Web of Science (WoS), Biomed Central, and PubMed. The following keywords were used: